2005
DOI: 10.1002/wcm.301
|View full text |Cite
|
Sign up to set email alerts
|

Automatic IEEE 802.11 rate control for streaming applications

Abstract: Streaming multimedia content in real-time over a wireless link is a challenging task because of the rapid fluctuations in link conditions that can occur due to movement, interference, and so on. The popular IEEE 802.11 standard includes low-level tuning parameters like the transmission rate. Standard device drivers for today's wireless products are based on gathering statistics, and consequently, adapt rather slowly to changes in conditions. To meet the strict latency requirements of streaming applications, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 7 publications
(6 reference statements)
0
29
0
1
Order By: Relevance
“…Drawing parallels with the IEEE 802.11a WiFi physical layer specification, that incorporates multi-rate transmission of up to 54Mbit/s [31], and recent work on rate-adaptive transmission [32] in the IR domain, if it is found that several environments have different received powers the following method can be applied. Firstly by normalising the I scaling factors, the equality result of (8) is independent of receiver power magnitude, and secondly for different environments we can adjust for example, the pulse characteristic, in order to increase or decrease the received power to make the power distributions equal.…”
Section: A Scaling Factorsmentioning
confidence: 99%
“…Drawing parallels with the IEEE 802.11a WiFi physical layer specification, that incorporates multi-rate transmission of up to 54Mbit/s [31], and recent work on rate-adaptive transmission [32] in the IR domain, if it is found that several environments have different received powers the following method can be applied. Firstly by normalising the I scaling factors, the equality result of (8) is independent of receiver power magnitude, and secondly for different environments we can adjust for example, the pulse characteristic, in order to increase or decrease the received power to make the power distributions equal.…”
Section: A Scaling Factorsmentioning
confidence: 99%
“…Drawing parallels with the IEEE 802.11a WiFi physical layer specification, that incorporates multi-rate transmission of up to 54Mbit/s [25], and recent work on rateadaptive transmission [26] in the IR domain, if it is found that several environments have different received powers, the following method can be applied. Firstly, by normalising the I scaling factors, the equality result of (9) is independent of receiver power magnitude, and secondly, for different environments, we can adjust for example, the pulse characteristic, in order to increase or decrease the received power to make the power distributions equal.…”
Section: The Channel Modelmentioning
confidence: 99%
“…Of course, there are many types of rate adaptation algorithms, but they all fundamentally rely in some way on these "trigger statistics" [3].…”
Section: Formal Analysismentioning
confidence: 99%
“…Delays become particularly critical in the case of real-time voice/video streaming applications, where the link conditions rapidly fluctuate due to mobility or interference. To address this problem, [3] proposes a hybrid SNR-based rate adaptation mechanism. However, this approach is limited by the very accuracy of the estimation possible in a closed-loop, low delay system -especially in the absence of standardized channel condition measurements (e.g.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation